IMPLEMENTATION OF GREEN UNIVERSITY BASED ON RAHMATAN LIL ALAMIN IN REALIZING ENVIRONMENTAL MANAGEMENT ACCOUNTING - Puspita, Silvia; Muchlis, Saiful; Jannah, Raodahtul (Islamic Financial And Accounting Review, 2025)
This study aims to examine the implementation of a Green University based on the values of Rahmatan Lil Alamin in realizing Environmental Management Accounting at the State Islamic University (UIN) Alauddin Makassar. The research employs a qualitative phenomenological approach and is conducted at UIN Alauddin Makassar, located in Gowa Regency, South Sulawesi. Primary data were collected through in-depth interviews with key informants, including the head of the planning bureau, commitment-making officials, lecturers, and students, as well as through direct observation. Secondary data were obtained from documentation, literature studies, and internet searches. The findings show that UIN Alauddin Makassar has implemented the Green University concept through environmental education, energy and water conservation, and the development of environmentally conscious infrastructure (green architecture). The values of Rahmatan Lil Alamin serve as an ethical and spiritual foundation in fulfilling environmental responsibilities through the relationship with God (hablum minallah), with fellow humans (hablum minannas), and with nature (hablum minal alam). The implementation of environmental management accounting is reflected in the allocation of budgets for environmental maintenance, evaluation of environmental performance, and strategies for reducing ecological impact. The integration of Islamic values with sustainability principles creates a campus management system that is both ecologically responsible and spiritually grounded.